2009
DOI: 10.2174/1874213000902010086
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Carbon Concentrations in the Stomach Content of Bank Voles (Myodes glareolus). Does Food Quality Determine Abundance?

Abstract: Abstract:We found that concentrations of nitrogen (N) in the stomach of voles varied between forest sites. Concentrations of nitrogen as well as the ratio of nitrogen to carbon (C) in stomach content were not different between the sexes or with season. Body mass varied between sites and between seasons but were unrelated to N concentration in spite that the body mass of voles in the spring season were on average 4.8 g heavier than in the autumn A positive relationship was found between N and C concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…In agreement with the results of previous studies, we found no relationship between body length, sex and age on the quality of food consumed by pygmy field mouse or common vole (Palo andOlsson 2009, Janova et al 2015), despite some studies observing improved food quality in breeding or sub-adult animals (Migula 1969, Obrtel and Holisova 1982, Cepelka et al 2014.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the results of previous studies, we found no relationship between body length, sex and age on the quality of food consumed by pygmy field mouse or common vole (Palo andOlsson 2009, Janova et al 2015), despite some studies observing improved food quality in breeding or sub-adult animals (Migula 1969, Obrtel and Holisova 1982, Cepelka et al 2014.…”
Section: Discussionsupporting
confidence: 92%
“…Further, the 'quality' of food in the stomachs did not change significantly, despite a considerable change in food availability following field set-aside and a consequent decrease in population and body size. Similarly, Palo and Olsson (2009) observed no relationship between N concentration in C. glareolus stomachs and body mass variation between sites and between seasons. A number of studies have confirmed an increase in the requirement for 'quality' food by females during reproduction; Migula (1969), for example, confirmed the increased energetic demand in reproducing common voles in laboratory experiments.…”
Section: Discussionmentioning
confidence: 76%
“…An increase in dietary quality (N level) concurrent with increasing common vole population density was also confirmed by Butet (1996) using classical chemical analysis; though in this case, the influence of sex or female breeding status was not considered. Similarly, Palo and Olsson (2009) noted that density was positively related to stomach N concentrations in bank vole Clethrionomys glareolus populations. These results suggest, therefore, that improved dietary quality may have a strong positive effect on survival and/or reproduction.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…For the bank vole (Myodes glareolus), both abundance and winter population declines have been related to food quality (Wereszczynska et al 2007;Palo and Olsson 2009). Selås (1997) suggested that Myodes voles increase in number after years with high production of bilberries because they benefit from improved food quality, caused by a trade-off between reproduction and defence in the plants.…”
Section: Introductionmentioning
confidence: 99%